Devolution and Black state legislators : challenges and choices in the twenty-first century - King-Meadows, Tyson, 1972- (SUNY series in African American studies., 2006)
"The Transformation of Plantation Politics explores the effects of black political exclusion, the sharecropping system, and white resistance on the Mississippi Delta's current economic and political situation. Sharon D. Wright Austin's extensive interviews with residents of the region shed light on the transformations and legacies of the Delta's political and economic institutions."--Jacket.